AN ANALYSIS OF ERRORS MADE BY THE THIRD GRADE STUDENTS OF METRO SCHOOL MAKASSAR - Masita, Maya (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
This research aimed at describing the kinds and the causes of errors made by the third grade students of Metro School Makassar in speaking English. The sample of this research was the third grade students of Metro School Makassar. The data collected by interview the students one by one through the use of video cameras by ArcSoft Webcam Companion 3 and then it was transcribed with Oxford Advanced Learner’s Dictionary to analyze the pronunciation. From the data it was found that there are seven types of errors in grammar and there are nineteen errors in pronouncing words during the interview. In grammar, errors in using verb groups are the most common errors made by the third grade students of Metro School Makassar. In pronunciation, errors in pronouncing the word ‘because’ is the most common errors made by the third grade students of Metro School Makassar. While the causes of errors are interlanguage transfer and intralingual transfer. It can be concluded that the students who have learned English language as a second language still confused by the structure of the English language.